The effect of epoxy resin on wood-plastic composites. Issue 5 (16th October 2018) - Feng, Chuanxin; Li, Zewen; Wang, Haosheng
Abstract : Purpose: This paper aims to investigate the effects of epoxy resin on the rheological and mechanical properties and water absorption rate of wood flour/high-density polyethylene (HDPE) composites (wood-plastic composite [WPC]). Design/methodology/approach: The reactive mixing of various epoxy resins with 60 Wt.% wood flour and HDPE was carried out in a twin-screw extruder with a special screw element arrangement. Polyethylene-grafted maleic anhydride (MAPE) was used as a coupling agent to improve the interfacial interaction between wood flour, epoxy resin and HDPE. Findings: The tensile, flexural and impact properties of the composites increased initially and then decreased with the increasing content of epoxy resin. The complex viscosity decreased with increasing epoxy resin content, but a trend reversal was observed at 8 Wt.% epoxy resin. The epoxy resin-modified wood-HDPE composites chemically coupled by MAPE showed minimal water absorption. Research limitations/implications: The cured epoxy resins impart high-aspect-ratio and plate-like polymeric fillers, affect the rheological behavior of the WPC and can also be oriented in a flow direction. Epoxy resin has good interaction with the cellulose structure of wood flour because of the polar functional groups within the cellulose. Practical implications: This method provided a simple and practical solution to improve the performance of WPC. Originality/value: The WPC modified by epoxy resin in this study had high performance in rheological and mechanical properties, and thus can be widely used for domestic, packaging and automotive applications.